Texas women’s decisions and experiences regarding self-managed abortion - Fuentes, Liza (BMC Womens Health, 2020)
BACKGROUND: Prior research has shown that a small proportion of U.S. women attempt to self-manage their abortion. The objective of this study is to describe Texas women’s motivations for and experiences with attempts to self-manage an abortion. The objective of this study is to describe Texas women’s motivations for and experiences with attempts to self-manage an abortion. METHODS: We report results from two data sources: two waves of surveys with women seeking abortion services at Texas facilities in 2012 and 2014 and qualitative interviews with women who reported attempting to self-manage their abortion while living in Texas at some time between 2009 and 2014. We report the prevalence of attempted self-managed abortion for the current pregnancy among survey respondents, and describe interview participants’ decision-making and experiences with abortion self-management. RESULTS: 6.9% (95% CI 5.2–9.0%) of abortion clients (n = 721) reported they had tried to end their current pregnancy on their own before coming to the clinic for an abortion. Interview participants (n = 18) described multiple reasons for their decision to attempt to self-manage abortion. No single reason was enough for any participant to consider self-managing their abortion; however, poverty intersected with and layered upon other obstacles to leave them feeling they had no other option. Ten interview participants reported having a complete abortion after taking medications, most of which was identified as misoprostol. None of the six women who used home remedies alone reported having a successful abortion; many described using these methods for several days or weeks which ultimately did not work, resulting in delays for some, greater distress, and higher costs. CONCLUSION: These findings point to a need to ensure that women who may consider self-managed abortion have accurate information about effective methods, what to expect in the process, and where to go for questions and follow-up care. There is increasing evidence that given accurate information and access to clinical consultation, self-managed abortion is as safe as clinic-based abortion care and that many women find it acceptable, while others may prefer to use clinic-based abortion care.